Encapsulating peritoneal sclerosis associated with burkholderia pseudomallei peritonitis - Zakaria, Nurul Aulia; Wan Ali, Wan Ahmad Syahril Rozli; Shahar, Mohammad Arif (Saudi Center for Organ Transplantation, 2018)
Burkholderia pseudomallei is a known motile organism in soil. Its infection is usually described in immunocompromised patients. It inflicts serious infection with high mortality and morbidity rate. We report a rare case of an end-stage renal disease patient on regular continuous ambulatory peritoneal dialysis (PD) who developed melioidosis PD peritonitis. Within a short period of time, she developed encapsulating peritoneal sclerosis evidenced by the intraoperative findings of intraabdominal cocooning. Choice and duration of antibiotic are important for proper eradication of the organism. Early diagnosis and treatment of both conditions also may improve the prognoses.